Edoxaban in atrial fibrillation with PCI by ACS or stable CAD presentation: a pre-specified analysis of the ENTRUST-AF PCI trial. (25th November 2020) - Vranckx, P; Valgimigli, M; Eckardt, L; Lewalter, T; Laeis, P; Reimitz, P.E; Smolnik, R; Zierhut, W; Tijssen, J; Goette, A
Abstract: Aim: We aimed to compare the safety and efficacy of edoxaban in combination with P2Y12 inhibition in the setting of percutaneous coronary intervention (PCI) in patients with atrial fibrillation (AF) presenting with an acute coronary syndrome (ACS) or stable coronary artery disease (SCAD). Methods and results: This is a pre-specified sub-analysis of the ENTRUST-AF PCI trial. Participants were randomly assigned 1:1 to an edoxaban or vitamin K antagonist (VKA) based strategy and randomisation was stratified by ACS (edoxaban n=388, vitamin K n=389) vs. SCAD (edoxaban n=363, vitamin K=366). Participants received edoxaban 60mg once daily plus a P2Y12 inhibitor for 12 months; or VKA in combination with a P2Y12 inhibitor and aspirin 100mg (for 1–12 months). The primary bleeding endpoint, a composite of International Society on Thrombosis and Haemostasis (ISTH) major or clinical relevant non-major bleeding, at 12 months occurred in 59 (18.52%/year) vs 79 (26.21%/year) ACS patients (Hazard ratio [HR] 0.73, 95% confidence interval [CI] 0.591–1.018, P=0.0631), and in 69 (23.11%/year) vs 73 (25.02%/year) SCAD patients (HR 0.94, 95% CI 0.676–1.305, P=0.7082) with edoxaban and VKA based therapies, respectively (P for interaction [P-int]=0.2741). The main efficacy endpoint (composite of cardiovascular death, myocardial infarction, stroke, systemic embolism, or definite stent thrombosis) occurred in 33 (9.59%/year) vs 28 (8.21%/year) ACS-patients (HR 1.16, 95% CI 0.697–1.916) compared with 16 (4.84%/year) vs 18 (5.47%/year) SCAD-patients (HR 0.91, 95% CI 0.465–1.781) with edoxaban and VKA based therapy, respectively (P-int=0.5573). Conclusions: An antithrombotic regimen consisting of edoxaban and a P2Y12-inhibitor without aspirin provides equal safety and similar efficacy for ischaemic events in patients with AF regardless of their clinical presentation with ACS or SCAD. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Daiichi Sankyo Europe GmbH